Exploring the Potential of Underutilized Legumes as Sustainable Protein Sources to Enhance Food Security and Nutrition: Global Perspectives and Insights from Nepal (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
Global food systems face unprecedented pressure from population growth, climate change, and resource degradation, intensifying the challenge of ensuring sustainable and nutritious diets. Protein insecurity remains particularly acute in developing regions, where high costs and environmental burdens constrain dependence on animal-based proteins. Underutilized legumes, including Bambara groundnut, winged bean, moth bean, and lupins, offer a promising yet overlooked solution. Rich in high-quality proteins, essential micronutrients, and bioactive compounds, these crops can improve nutrition, mitigate malnutrition, and reduce the prevalence of non-communicable diseases. Agronomically, their adaptability to marginal environments, drought resilience, and nitrogen-fixing ability enhance soil fertility and promote climate-smart agriculture, aligning directly with Sustainable Development Goals (SDGs 2, 12, and 13). However, barriers such as limited genetic improvement, processing constraints, weak markets, and cultural unfamiliarity hinder their wider adoption.This research explores underutilized legumes' nutritional, environmental, and economic potential while addressing consumer acceptance and value chain integration challenges. Using a multidisciplinary approach, it incorporates laboratory analysis, processing innovations (germination, fermentation, extrusion), sensory evaluations, and environmental impact assessments. A case study from Nepal highlights both opportunities and constraints. Legumes such as lentils, chickpeas, soybeans, and indigenous pulses already contribute significantly to national food security and exports. Yet, productivity gaps, lack of improved varieties, and limited extension services continue to restrict their impact. Enhancing awareness, strengthening seed systems, and developing inclusive markets can unlock their potential to support smallholder livelihoods and dietary diversity.By bridging scientific research, consumer behavior, and policy frameworks, this study emphasizes the transformative role of underutilized legumes in fostering resilient food systems, advancing nutrition security, and promoting ecological sustainability in Nepal and beyond.